Multifractal Analysis Reveals Decreased Non-linearity and Stronger Anticorrelations in Heart Period Fluctuations of Fibromyalgia Patients - Reyes-Manzano, Cesar F.; Lerma, Claudia; Echeverría, Juan C.; Martínez-Lavin, Manuel; Martínez-Martínez, Laura A.; Infante, Oscar; Guzmán-Vargas, Lev (Frontiers in Physiology, 2018)
Objective: To characterize the multifractal behavior of the RR fluctuations in fibromyalgia patients (FM) in comparison with healthy-matched subjects. Methods: Multifractral detrended fluctuation analysis (MDFA) was used to study multifractality in heartbeat times-series from 30 female healthy subjects and 30 female patients with fibromyalgia during day and night periods.The multifractal changes as derived from the magnitude and sign analysis of these RR fluctuations were also assessed. Results: The RR fluctuations dynamics of healthy subjects showed a broad multifractal spectrum. By contrast,a noticeable decrease in multifractality and nonlinearity was observed for patients with fibromyalgia. In addition, the spectra corresponding to FM subjects were located on the average to the right of the spectra of healthy individuals, indicating that the local scaling exponents reflect a smoother behavior compared to healthy dynamics. Moreover, the multifractal analysis as applied to the magnitude and sign heartbeat series confirmed that, in addition to a decreased nonlinearity, fibromyalgia patients presented stronger anticorrelation in directionality, which did not remain invariant for small or rather larger fluctuations as it occurred in healthy subjects. Conclusion: When compared to healthy controls, fibromyalgia patients display decreased nonlinearity and stronger anticorrelations in heart period fluctuations. These findings reinforce the hypothesis of the potential role of the dysfunctional autonomic nervous system in the pathogenesis of fibromyalgia.